Surgical Management of a Rare Case of Massive Compound Odontome Associated with Missing Primary Tooth - Elengkumaran Sankaran; Sangeetha Narasimhan; KS Sabitha; Punit Chitlangia (Journal of Clinical and Diagnostic Research, 2017)
Odontomes are considered to be the most common odontogenic tumours of the jaws. They are benign, mixed tumours arising from the remnants of both odontogenic epithelium and the ectomesenchyme resulting in the deposition of varied propotions of enamel, dentin, cementum and pulp tissues. As these lesions show deficiency only in structural arrangement, some authors consider odontomes as hamartomas or tumour like malformations. Though these lesions are more common in children, very few cases have been reported in less than five years age group. Blood loss is a major issue in paediatric surgery. Careful and safe surgery is the primary goal of the surgeon. The external carorid artery which is the only feeder of blood to the face and oral cavity can be ligated to control bleeding in extensive maxillofacial injuries and orofacial malignancies. Herewith, we report a massive odontome in a three and half-year-old child which was treated by surgical excision along with carotid control to prevent excess bleeding.